(untitled) (مجلة إحالات, 2026)
The poetry of enthusiasm occupies an important place in the consciousness of the Arabic and its afflictions of the pre-Islamic era and beyond, as systems of poetry in which language translates the role of the sword , and the words replace the acts, immortalize the knights of the warriors who built their glory on the spearheads and expressed their amusement What tends to noble values such as courage, courage, generosity, riding and sacrifice to defend honor and preserve glory and the good male, was the most important verse of poetry that included a number of enthusiastic poems: the Abu Tammam office, which enjoyed great prestige in old Arabic poetry, and reached the spread and appropriation of his status unless reported by Dew N other, also received the language specialists of interest and criticism of poetry and the appreciation in various scientific circles. Having achieved the admiration of some writers and their endorsement for him, they declared: "Abba Tamam, in his choice of enthusiasm, the meaning in his hair", influenced by his student Bahtri, who walked in his steps to collect enthusiastic poems and the classification of his office. The enthusiasm of the East - Abu Tammam - moved to the Maghreb and received a positive response; the most important was influenced by him and followed his path in the program and the presentation in a big and a thousand enthusiasts corresponds to the Court, enthusiasm to the measure of the Moroccan enthusiasm and . enthusiasm, Son of Andalusian